Alterations in the hepatic transcriptional landscape after RNAi mediated ApoB silencing in cynomolgus monkeys. Issue 2 (October 2015) - Hamza, M. Sabry; Kumar, Chanchal; Chia, Ser Mien; Anandalakshmi, Vidhya; Boo, Nicole; Strapps, Walter; Robinson, Michael; Caguyong, Michelle; Bartz, Steven; Tadin-Strapps, Marija; van Gool, Alain; Shih, Shian-Jiun
Abstract The greater genomic conservation between humans and non-human primates (NHP) enables target validation studies for developing of therapeutic strategies for human diseases. Together with predicting activity and potential adverse clinical signs, the inclusion of NHP testing bequeaths to efficacy models for dose titration and pharmacodynamic effects. We have used lipid nanoparticle encapsulated siRNA to silence ApoB in the liver and assessed the phenotypic effects on serum lipids with various levels of hepatic ApoB mRNA knockdown in healthy lean cynomolgus monkeys. ApoB siRNA dosed animals demonstrated significant reductions of hepatic ApoB mRNA and serum APOB protein, with a substantial lowering of plasma lipid levels without obvious signs of toxicity. Microarray based assessment of ApoB siRNA mediated effects revealed a number of differentially expressed genes which mapped onto biological pathways and processes related to lipid and cholesterol metabolism. Furthermore, we identified potential targets and cellular effects that could be studied for therapeutic benchmarking of APOB mediated effects. The network of ApoB regulated genes should be of significance for the understanding and development of novel hypercholesterolemia therapies.